2004
DOI: 10.1191/1352458504ms1112oa
|View full text |Cite
|
Sign up to set email alerts
|

Decisional role preferences, risk knowledge and information interests in patients with multiple sclerosis

Abstract: Patients with MS claimed autonomous roles in their health care decisions. The weak correlation between knowledge and preferences for active roles implicates that other factors largely influence role preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
147
3
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(162 citation statements)
references
References 27 publications
11
147
3
1
Order By: Relevance
“…Finally, the findings of this quantitative study described the low and moderate levels of awareness. These results are consistent with the findings of the study by Hansen et al [32] They found that 79% of patients tend to acquire the necessary knowledge about disease progression, duration of disease and disease control practices. In a study performed in 2012 Heydari and Shahbazi [33] found that if the elderly have accurate information about proper practices of nutrition, exercise, sleep and rest, and proper use of drugs, many of their problems can be avoided or, if created, can be well-managed, and steps can be taken to improve their quality of life.…”
Section: Discussionsupporting
confidence: 83%
“…Finally, the findings of this quantitative study described the low and moderate levels of awareness. These results are consistent with the findings of the study by Hansen et al [32] They found that 79% of patients tend to acquire the necessary knowledge about disease progression, duration of disease and disease control practices. In a study performed in 2012 Heydari and Shahbazi [33] found that if the elderly have accurate information about proper practices of nutrition, exercise, sleep and rest, and proper use of drugs, many of their problems can be avoided or, if created, can be well-managed, and steps can be taken to improve their quality of life.…”
Section: Discussionsupporting
confidence: 83%
“…In Vorstudien konnte gezeigt werden, dass bis zu 75 der Patienten aktiv mitentscheiden möchten [22] und die Fähigkeit von MS-Patienten, Risikokalkulationen durchzuführen, durch das Üben mit entsprechenden Krankheitsinformationen signifikant erhöht werden kann [21].…”
Section: Multiple Skleroseunclassified
“…Heesen et al 19 and Kopke et al 20 suggest that MS lends itself to a shared decision-making model. Of 1374 patients, these authors found that most preferred shared decision making or informed choice as their method of decision making (Figure 1).…”
Section: Patient's Rolementioning
confidence: 99%
“…19 Patients often must choose between four injectable therapies that, although effective, are not cures and are regarded by some clinicians as comparable in efficacy. In addition, patients must cope with symptoms daily, which range from mildly annoying to extremely debilitating.…”
Section: Patient's Rolementioning
confidence: 99%